Teaching perspective during COVID-19: coping and stress - Ana Maria Cossio Ale de Preciado; José Gregorio Brito-Garcías (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study aimed to analyze the indicators related to coping and stress or burnout perceived by teachers who worked virtually during the COVID-19 pandemic; it presented a descriptive quantitative approach. The data collection technique used was a survey and a self-administered questionnaire as the instrument used, structured in five dimensions: stressful situations during virtual work, perceived feelings, teacher coping, perception of optimism, and lifestyle assumed due to the pandemic. The sample selected for the study was composed of 97 teachers who experienced virtual teaching in various regions of Peru. The study concluded that teachers experienced stressful situations, made strong sacrifices, faced and sought alternatives, and were assertive and calm. They have had both positive and negative feelings about remote education. This survey showed optimistic changes, making teachers strive to adopt a new lifestyle dedicated to training independently and improving technological skills, among other aspects